PENGARUH INDEPENDENSI AUDITOR, AUDITOR EKSTERNAL DAN MEKANISME CORPORATE GOVERNANCE TERHADAP INTEGRITAS LAPORAN KEUANGAN PERUSAHAAN LQ45 YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2010 â 2013 - Aji Pambudi Utomo, 10.05.52.0088; Himawan, Arief (Students Journal of Accounting and Banking, 2016)
Integrity of financial statements is the extent to which the financial statements are presented with the right information and honest. This study examines the effect of auditor independence, quality audit and corporate governance mechanisms on the integrity of financial statements. This study uses the companys financial statements are included in the LQ45 in Indonesia Stock Exchange in 2010-2013 as many as 45 companies setian year. Samples in this study were 23 companies LQ45 fourth consecutive year - were listed on the Indonesia Stock Exchange in 2010 - 2013. The data used in this research is secondary data and sample selection companies using purposive sampling and analysis methods using multiple regression analysis. Results of testing the hypothesis in this study showed that only one variable which is a measure of the board of commissioners positive effect on the integrity of financial statements, while the independence of auditors, external auditors, the number of audit committee, the number of independent directors, institutional ownership, ownership manajerian not affect the integrity of financial statements. Keywords: Auditor Independence, Corporate Governance, Integrity of Financial Statements